GIS And Remote Sensing Methods Based Assessment of the State of Ground Water Resources with Special References to Western Indian River Basins: Utilizing GIS and Remote Sensing Methods for Groundwater Assessment in Western Indian River Basins (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The accessible water ought to be prudently used through legitimate improvement and the executives systems. The point of this assessment is to contribute towards efficient groundwater ponders utilizing Remote Sensing, Field Studies, remote sensing and GIS in making ground-breaking rules for groundwater resource assessment in equivalent hydrological domains. The Godavari river basin of western Maharashtra is waterway water system framework, significant development crops are paddy and sugarcane. Likewise, the methodology at effectively in the areas with equivalent environment and geology, for instance Western Indian River Basins which encounters serious absence of water driving.